2020
DOI: 10.1177/2325967120911126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intra-articular Ketorolac Versus Corticosteroid Injection for Knee Osteoarthritis: A Retrospective Comparative Study

Abstract: Background: Intra-articular corticosteroid injections have been widely used and are considered a mainstay in the nonoperative treatment of symptomatic knee osteoarthritis (OA). However, their increased use can have negative implications, including chondral toxicity and a high risk of infections. As a result, nonsteroidal anti-inflammatory drugs have been considered as an alternative. Purpose: To determine the pain relief and safety of ketorolac versus a corticosteroid to supplement an intra-articular sodium hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…[18][19][20] Jianda et al in a study of 84 patients of knee OA comparing corticosteroids with ketorolac reported similar analgesic and functional outcomes, with a success rate of 59.5% in corticosteroids and 57.1% in the k group. 18 In our study, there was an insignificant difference between the mean WOMAC score at 18 In another study mean VAS scored decreased in both patient groups that either received Ketorolac or Triamcinolone and no statistical difference was found (p-value=0.98). 19 However, patients receiving corticosteroids have a better functional outcome as compared to those receiving NSAIDs.…”
Section: Discussionmentioning
confidence: 89%
“…[18][19][20] Jianda et al in a study of 84 patients of knee OA comparing corticosteroids with ketorolac reported similar analgesic and functional outcomes, with a success rate of 59.5% in corticosteroids and 57.1% in the k group. 18 In our study, there was an insignificant difference between the mean WOMAC score at 18 In another study mean VAS scored decreased in both patient groups that either received Ketorolac or Triamcinolone and no statistical difference was found (p-value=0.98). 19 However, patients receiving corticosteroids have a better functional outcome as compared to those receiving NSAIDs.…”
Section: Discussionmentioning
confidence: 89%
“…Use of ketorolac has been studied in knee OA showing similar improvements in pain and knee function compared with triamcinolone, although its efficacy in BCs has not been established. 25 Aspiration and corticosteroid injection of BCs have been previously studied specifically in atraumatic patients with a history of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…[90][91][92][93] Studies evaluating the intra-articular administration of ketorolac compared with intra-articular triamcinolone acetonide in human patients with knee OA found similar efficacy and significant improvement in pain scores in both groups. 91,92 Studies evaluating the safety of intra-articular NSAIDs in human and animal models have found mixed results and further research is needed to investigate the effects on cartilage and soft tissue structures. 90,93 In horses, few studies have been performed evaluating the intra-articular use of NSAIDs or sustained drug release products.…”
Section: Local Delivery Of Nsaidsmentioning
confidence: 99%
“…Additional benefits of local administration include the requirement of a lower dose, the ability to use drugs with a low bioavailability, decreased systemic side effects and longer intervals between treatments. In human medicine, intra‐articular administration of ketorolac for treatment of OA and postoperative pain has shown promising results 90‐93 . Studies evaluating the intra‐articular administration of ketorolac compared with intra‐articular triamcinolone acetonide in human patients with knee OA found similar efficacy and significant improvement in pain scores in both groups 91,92 .…”
Section: Assessment Of the Future Management Of Pain And Inflammation...mentioning
confidence: 99%
See 1 more Smart Citation